Germination Potential of Dormant and Nondormant Arabidopsis Seeds Is Driven by Distinct Recruitment of Messenger RNAs to Polysomes - Basbouss-Serhal, Isabelle (Plant Physiol, 2015)
Dormancy is a complex evolutionary trait that temporally prevents seed germination, thus allowing seedling growth at a favorable season. High-throughput analyses of transcriptomes have led to significant progress in understanding the molecular regulation of this process, but the role of posttranscriptional mechanisms has received little attention. In this work, we have studied the dynamics of messenger RNA association with polysomes and compared the transcriptome with the translatome in dormant and nondormant seeds of Arabidopsis (Arabidopsis thaliana) during their imbibition at 25°C in darkness, a temperature preventing germination of dormant seeds only. DNA microarray analysis revealed that 4,670 and 7,028 transcripts were differentially abundant in dormant and nondormant seeds in the transcriptome and the translatome, respectively. We show that there is no correlation between transcriptome and translatome and that germination regulation is also largely translational, implying a selective and dynamic recruitment of messenger RNAs to polysomes in both dormant and nondormant seeds. The study of 5′ untranslated region features revealed that GC content and the number of upstream open reading frames could play a role in selective translation occurring during germination. Gene Ontology clustering showed that the functions of polysome-associated transcripts differed between dormant and nondormant seeds and revealed actors in seed dormancy and germination. In conclusion, our results demonstrate the essential role of selective polysome loading in this biological process.